Influence of mixing time during glycine–nitrate process on the structural properties and reducibility of a dual-phase Ni–Cu–Mn spinel catalyst. Issue 24 (15th December 2021) - Aznam, Isyraf; Mah, Joelle C.W.; Muchtar, Andanastuti; Baharuddin, Nurul Akidah; Somalu, Mahendra R.; Muhamud, Rahimi L.
Abstract: The potential of Ni–Cu–Mn spinels as methane reforming catalysts for hydrocarbon-fueled solid oxide fuel cell (SOFC) applications is highly dependent on its catalytic properties, particularly reducibility. The reducibility of a spinel-structured catalyst is often correlated with its structural properties and fabrication processes. In this work, the structural properties and reducibility of a Ni–Cu–Mn spinel catalyst was evaluated on the basis of mixing time during the glycine–nitrate process. Phase analysis results showed that Ni0.4 Cu0.6 Mn2.0 O4 and (Cu, Mn)3 O4 in normal or inversed spinel structures were observed in GNP-produced Ni–Cu–Mn spinel catalyst powders. Distortion in inverse spinel structures enhanced the reducibility of the spinel catalyst. Morphological analysis results showed that complete nitrate binding occurred at a minimum mixing time of 24 h and resulted in homogenous particle size distribution and uniform elemental distribution. Furthermore, the Ni–Cu–Mn spinel catalyst produced after 24 h of mixing was fully reduced at 450 °C. The reducing pattern of the Ni–Cu–Mn spinel catalyst produced after 24 h of mixing time showed strong metal–support interaction and the fast adsorption of reactants. These effects were due to either the distribution of divalent cations in octahedral sites or large amounts of bulk pores. In conclusion, a minimum mixing time of 24 h is sufficient to produce the desired structural properties and reducibility of Ni–Cu–Mn spinel catalysts for SOFC applications.